Convergence to natural prices in simple production - Ian Wright (The Open University, Economics Department, 2011)
This paper describes a nonlinear dynamic model of the convergence of market prices to natural prices in a multisector simple production economy under conditions of a constant technique and composition of demand. Prices and quantities adjust in real time according to the classical principle of cross-dual dynamics. The economy gravitates toward an asymptotically stable equilibrium in which natural prices are proportional to labor-values. To demonstrate an application of the model we reply to Mirowski's (1989) critique that Marx held a contradictory substance and field theory of value.
Keywords: 330; Preistheorie; Anpassung; Theorie